2021
DOI: 10.1111/ced.14762
|View full text |Cite
|
Sign up to set email alerts
|

Line‐field optical coherence tomography: in vivo diagnosis of basal cell carcinoma subtypes compared with histopathology

Abstract: Background. Basal cell carcinoma (BCC) is the most common skin cancer in the general population. Treatments vary from Mohs surgery to topical therapy, depending on the subtype. Dermoscopy, reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) have gained a foothold in daily clinical practice to optimize diagnosis and subtype-oriented treatment. The new technique of line-field confocal OCT (LC-OCT) allows imaging at high resolution and depth, but its use has not yet been investigated in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 32 publications
5
59
0
4
Order By: Relevance
“…Through a backward elimination approach, non-significant parameters were removed one by one so that the three most impactful parameters to discriminate between BCC and non-BCC were: poorly defined DEJ, dark rim/clefting, and hyporeflective ovoid structures. These findings were in line with previous work [ 10 , 11 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Through a backward elimination approach, non-significant parameters were removed one by one so that the three most impactful parameters to discriminate between BCC and non-BCC were: poorly defined DEJ, dark rim/clefting, and hyporeflective ovoid structures. These findings were in line with previous work [ 10 , 11 ].…”
Section: Resultssupporting
confidence: 94%
“…Suppa et al examined 89 BCCs and described tumor lobules, with (in superficial BCCs) or without connection (in nodular BCCs) to the epidermis and branched lobules (in infiltrative BCCs). In our previous study [ 11 ], we reported overlapping findings and defined, analogously to OCT terminology, the presence of a string of pearls pattern in superficial BCCs and of a shoal of fish pattern in infiltrative BCCs. Moreover, we reported an overall BCC subtype agreement between LC-OCT and histology of 90.4%, with a sensitivity of 82% and a specificity of 100% for superficial BCCs.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations